Three-dimensional virtual histology of benign and malignant endometrial stromal neoplasms: a new perspective on why morphology matters - Kommoss, Felix; Albers, Jonas; Schwab, Constantin; Wagner, Willi Linus; Tromba, Giuliana; Dullin, Christian (International journal of gynecological cancer, 2021)
A perimenopausal woman presented with a history of hypermenorrhea and enlargement of uterine fibroids. Histopathological examination of curettage material showed fragments of a mesenchymal neoplasm consisting of small and monomorphic spindle cells with scant cytoplasm, reminiscent of non‐